IMPLEMENTASI SOCIAL CUSTOMER RELATIONSHIP MANAGEMENT DALAM MENINGKATKAN PROMOSI PRODUK - Siregar, Annisa Yasmin (Journal of Data Analytics, Information, and Computer Science, 2024)
Nibra's House Sukarami Palembang is a Muslim store and marketplace that hadn’t fully used its product promotions. Based on the that statement, Social Customer Relationship Management (Social CRM) was implemented at Nibra's House Sukarami Palembang with the goal of increasing the product promotions. The system is being developed using the FAST system development methodology and makes use of social media platforms, specifically Facebook and Instagram of Nibra's House Sukarami Palembang. The study's finding is a Social CRM system built on a website using PHP programming language and MySQL database management system. It also optimizes customer relationship management via the usage of social media platforms: Facebook and Instagram of Nibra's House Sukarami Palembang.  Keyword : Product Promotion, Customer, Social CRM, PHP, My SQL, Facebook, Instagram